The Use of Commercial Advertisement to Teach University Students in English for Specific Purpose Context - Utami, Fajar Dwi; Tyas, Mei Ardaning; Mustika, Nurika (Lingua Cultura, 2019)
This research aimed to propose multimodal-based English teaching through video for university students majoring in marketing management through project-based learning. Teaching English for university students are belonging to the field of English for Specific Purposes (ESP). It needs special treatments due to the fact that ESP students have different needs for English use for their future jobs, since the industrial revolution 4.0 typically affected the economic area. For presenting the research, the qualitative research design was employed. This research used interpretive analysis in the context of discourse analysis. The commercial advertisement video was analyzed in terms of Systemic Functional Linguistics (SFL) and semiotic features of multimodal discourse analysis. The analysis results of the video show that semiotic features are more powerful than linguistics aspects in promoting goods well. The video is expectedly used to teach language for promotion to the university students, particularly in marketing management majors. The teaching-learning process would be guided by the use of project-based learning method so that the outcomes would be in the form of the promotional video which employs both linguistics and semiotic features.Â